Psycholinguistic Markers of Students’ Ethnic Intolerance Manifestation - Kykhtiuk, Oksana; Solovey , Oksana (East European Journal of Psycholinguistics, 2015)
The article is focused on the theoretical and empirical study of psycholinguistic markers of students’ ethnic intolerance manifestation. The authors offer basic approaches to definitions of ethnic tolerance, ethnic identity, ethnic prejudices and ethnic stereotypes. The empirical study involved the revealing of social distance, social role, which determine the type of ethnic identity of respondents, and psycholinguistic markers of ethnic intolerance manifestation. It has been found out that i) 48.9 per sent of all respondents have positive ethnic identity, which is characterized by a combination of positive attitudes towards their own people as well as a positive attitude to other people; ii) 30.2 per cent of the respondents were  identified as ethnically indifferent, i.e. with blurred ethnic identity, expressed in uncertainty of  ethnicity; iii) 20.9 per cent of the respondents expressed verbally their ethnic intolerance.  This fact can cause tension and irritation in communication with other ethnic groups or recognition of the rights of others. The results of the present empirical study has shown that the students had positive underlying autostereotypes towards own ethnic group. However, there were some ethnic prejudices as to Russians, surface negative stereotypes as to Germans as members of other ethnic groups.ReferencesAboud, F. (1994). Children and Prejudice. Oxford: Blackwell Publishers.Gasanov, I. (1994). Natsionalnye stereotypy i obraz vraga [National stereotypes and theimage of the enemy]. Moscow: Progress.Gnatenko, P. (1995). Etnicheskie ustanovki i etnicheskie stereotypy [Ethnic guidelineand ethnic stereotypes]. Dnipropetrovsk: Dnipropetrovsk State University.Ivanova, N. (2004). Identichnost i tolerantnost: sootnoshenie etnicheskikh iprofesionalnykh stereotipov [Identity and tolerance: the ratio of professional and ethnicstereotypes]. Voprosy Psyhologii, 6, 54–63.Kykhtiuk, O. (2010). Psykholoрichni osoblyvosti formuvannja etnichnoji tolerantnosti ustudentskoji molodi [Psychological peculiarities of forming ethnic tolerance in student youth].Ph.D. thesis. Lutsk: Volyn National University.Soldatova, G. (2006). Psykhologicheskie mekhanizmy ksenofobii [Psychologicalmechanisms of xenophobia]. Psykhologicheskiy Zhurnal, 27(6), 5–17.Zasiekina, L. (2008). Fenomen tolerantnosti kriz pryzmu etnichnogo dyskursu [Thephenomenon of tolerance from ethnic discourse perspective]. Psykholohichni Perspektyvy, 11,99–109.